User Centric Design: A Framework for Transforming Design Studios into Smart Workspaces - Megha Jain; Deepti Pande Rana (International Journal of Optical Innovations & Research, 2024)
In contemporary design studios, the integration of smart technologies has become imperative to enhance productivity, collaboration, and creativity among designers. This research paper presents a comprehensive framework for the transformation of conventional design studios into smart workspaces, focusing on user-centric design principles. The concept of User-Centric Design emphasizes its departure from traditional design approaches by placing the user experience at the forefront of the creative process. It highlights the increasing importance of adapting design studios to meet the evolving needs and expectations of individuals working in these environments. By amalgamating insights from user-technology interaction, user experience design, and workspace management, this framework offers a structured approach to cater to the diverse needs and preferences of designers. The proposed framework encompasses various dimensions, including physical infrastructure, digital tools, communication channels, and ergonomic considerations, all aimed at fostering an environment conducive to innovation and efficiency. Through a synthesis of theoretical perspectives and practical case studies, this paper elucidates the key components of the framework and their respective implementation strategies. Furthermore, this research emphasizes the iterative nature of design processes and advocates for continuous adaptation and refinement of smart workspace configurations based on user feedback and evolving technological advancements. By prioritizing the needs and experiences of designers, this framework endeavors to empower individuals and teams to unleash their full creative potential while leveraging the capabilities of smart technologies. Ultimately, this paper contributes to the discourse on user-centric design by providing actionable insights and guidelines for the integration of smart technologies in design studios, thereby facilitating the creation of dynamic and collaborative work environments that inspire innovation and excellence.
Keywords: Innovation; User-centric design; collaborative work environments; design studios; digital tools; ergonomic; iterative design processes; smart technologies; smart workspaces; technological advancements; user feedback; user-technology interaction